Membrane-Bound Catechol-O-Methyl Transferase in Cortical Neurons and Glial Cells is Intracellularly Oriented - Schott, Björn H.; Frischknecht, Renato; Debska-Vielhaber, Grazyna; John, Nora; Behnisch, Gusalija; Düzel, Emrah; Gundelfinger, Eckart D.; Seidenbecher, Constanze I. (Frontiers in Psychiatry, 2010)
Catechol-O-methyl transferase (COMT) is involved in the inactivation of dopamine in brain regions in which the dopamine transporter (DAT1) is sparsely expressed. The membrane-bound isoform of COMT (MB-COMT) is the predominantly expressed form in the mammalian central nervous system (CNS). It has been a matter of debate whether in neural cells of the CNS the enzymatic domain of MB-COMT is oriented towards the cytoplasmic or the extracellular compartment. Here we used live immunocytochemistry on cultured neocortical neurons and glial cells to investigate the expression and membrane orientation of native COMT and of transfected MB-COMT fused to green fluorescent protein (GFP). After live staining, COMT immunoreactivity was reliably detected in both neurons and glial cells after permeabilization, but not on unpermeabilized cells. Similarly, autofluorescence of COMT-GFP fusion protein and antibody fluorescence showed overlap only in permeabilized neurons. Our data provide converging evidence for an intracellular membrane orientation of MB-COMT in neurons and glial cells, suggesting the presence of a DAT1-independent postsynaptic uptake mechanism for dopamine, prior to its degradation via COMT.